MODEL PEMBELAJARAN BERBASIS PROJEK DALAM MEMPRODUKSI TEKS CERPEN DI SMA - Rasyad, Sobihah; Susilo, Jimat; Casmanto, Casmanto (BAHASTRA, 2017)
Based on a preliminary study conducted in some high schools, most of the students experienced difficulties in writing their ideas in the form of short stories. This research, therefore, aimed at assisting students and teachers in producing short stories. The proposed solution is applying an instructional model based on projects. This research used quasi-experimental research method using non-equivalent control group design. This study took 60 students randomly as the sample from 385 students. The result shows that the mean of the experiment class was 91.43%, which was categorized as very good. The project-based instructional model was also effective based on a t-test calculation with its score of 7.45 >2.04.